Effective Cds:(Ce, Ga) Nanoparticles for Photocatalytic h2 Production Under Artificial Solar Light Exposer - Radhalayam, D (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
To encounter the burgeoning energy demands of the future, it is imperative to focus on the progress of innovative and profitable techniques for hydrogen (H2) evolution, coupled with an enriched stability of photocatalysts. In this work, we have effectually prepared CdS, CdS:Ce, and CdS:(Ce, Ga) nanoparticles through a chemical refluxing method at 120 °C. Comprehensive structural analysis confirmed the effectual incorporation of Ce and Ga ions in the place of Cd2+ in a CdS matrix. Morphology analysis indicates that the prepared samples are irregularly shaped nanoparticles. Chemical analysis confirmed that the Ce and Ga ions incorporated in the Cd site occurred with 3+ and 4+ valence states. All the samples were assessed for H2 production through water splitting via artificial solar light irradiation. Amid all the samples, CdS:(Ce, Ga) nanoparticles portrayed a giant H2 evolution efficacy (3012 µmol h−1g−1) in 300 min, which is 13.9 times larger than that of the bar CdS sample. Thus, we firmly propose that CdS:(Ce, Ga) samples are authentic and potent candidates for efficient photocatalytic H2 production in sterile environments. © 2025 by the authors.